Gender Differences in Mathematical Proficiency: A Review of Mathematics Performance - Syarifuddin, Muhammad (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2025)
Mathematical proficiency is developed in students to be able to solve problems faced in everyday life appropriately and efficiently. This study focuses on one of the things that influences students' abilities, namely gender. This study aims to describe the process of mathematical proficiency in solving problems based on gender. The instruments of this study were a mathematical ability test, a mathematical proficiency test, and an interview guideline. The mathematical ability test was distributed to 136 students who were members of the natural sciences interest in one of the high schools in Kendari City. Students who meet the specified criteria, namely having mathematical abilities equivalent to different genders, will be selected as research subjects. In this study, differences were found between male and female in solving problems, namely, male subjects can formulate and represent problems, can understand concepts, and apply procedures well so that they can solve problems, while female subjects can understand concepts, can formulate and represent problems, and do not choose procedures correctly so that they cannot solve problems correctly. In addition, they also have similarities, namely that both subjects represent problems with pictures, can explain the relationship between concepts and problems, and get ideas for solving problems based on everyday experiences. The productive disposition ability of male subjects supports in determining the strategies used in solving problems, while female subjects are less supportive in solving problems.